2016
DOI: 10.1159/000448884
|View full text |Cite
|
Sign up to set email alerts
|

Transmural Colonic Infarction after Routine Colonoscopy in a Young Patient without Risk Factors

Abstract: Colonoscopy is one of the most widely used procedures in medical practice for the diagnosis and treatment of many benign and malignant diseases of the colorectal tract. Colonscopy has become the reference procedure for screening and surveillance of colorectal cancer. The overall rate of adverse events is estimated to be about 2.8 per 1,000 procedures, while complications requiring hospitalization are about 1.9 per 1,000 colonoscopies. Mortality from all causes and colonoscopy-specific mortality are estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…An extensive search of the literature showed 25 reports of colonoscopy-related colonic ischemia[ 22 ]. The first report in 1990 described a young woman with a history of systemic lupus erythematosus who developed abdominal pain and bloody diarrhea after a diagnostic colonoscopy.…”
Section: Colonic Ischemia After Colonoscopymentioning
confidence: 99%
See 3 more Smart Citations
“…An extensive search of the literature showed 25 reports of colonoscopy-related colonic ischemia[ 22 ]. The first report in 1990 described a young woman with a history of systemic lupus erythematosus who developed abdominal pain and bloody diarrhea after a diagnostic colonoscopy.…”
Section: Colonic Ischemia After Colonoscopymentioning
confidence: 99%
“…These include the sudden onset of abdominal pain associated with nausea, vomiting, bloating, and passage of bright bloody diarrhea within 24 h, which often evolve in melena[ 8 ]. Zizzo et al [ 22 ] found that abdominal pain and bloody diarrhea were present in 95% of patients reported to have colonic ischemia after colonoscopy. Moreover, it is assumed that a non-negligible number of cases may be paucisymptomatic and thereby go undetected.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional identified risk factors include hypertension, cardiovascular disease, and diabetes mellitus [ 7 , 8 ]. Interestingly, colonoscopy itself has been described in the literature as a cause of IC with 25 studies identified globally [ 9 ]. In these case reports, we describe two cases of IC following colonoscopy with Bi-Peglyte (15 mg Bisacodyl/PEG 3350) used as bowel preparation.…”
Section: Introductionmentioning
confidence: 99%